2018
DOI: 10.7567/apex.11.122501
|View full text |Cite
|
Sign up to set email alerts
|

Millisecond-order X-ray phase tomography with a fringe-scanning method

Abstract: We successfully realized millisecond-order X-ray phase tomography using a fringe-scanning method in grating-based X-ray interferometry. We obtained phase tomograms with a measurement time of 4.43 ms using a white synchrotron X-ray beam. The use of a fringe-scanning method enables us to achieve not only a higher spatial resolution but also a higher signal-to-noise ratio than that attained by the Fourier transform method. In addition, our approach can be applied to realize four-dimensional or high-throughput X-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…Time-resolved radioscopy for very short exposure times (down to 100 ps per image) and 1 Mfps repetition rate is possible 47 , but acquisition is limited to very short periods, thus not allowing to follow longer processes continuously. Tomography naturally has been much slower than radioscopy but some proofs of concept on solid samples have shown that acquisition rates of 100 tps are feasible 48 . The state of the art in fast and high-resolution tomographic microscopy (we consider here voxel sizes smaller than 10 µm) applied to dynamically evolving materials is 20−25 tps 40,45,49 .…”
Section: Methodsmentioning
confidence: 99%
“…Time-resolved radioscopy for very short exposure times (down to 100 ps per image) and 1 Mfps repetition rate is possible 47 , but acquisition is limited to very short periods, thus not allowing to follow longer processes continuously. Tomography naturally has been much slower than radioscopy but some proofs of concept on solid samples have shown that acquisition rates of 100 tps are feasible 48 . The state of the art in fast and high-resolution tomographic microscopy (we consider here voxel sizes smaller than 10 µm) applied to dynamically evolving materials is 20−25 tps 40,45,49 .…”
Section: Methodsmentioning
confidence: 99%
“…Although its sensitivity is lower than that of X-ray crystal interferometry (Yoneyama et al, 2006(Yoneyama et al, , 2018Takeda et al, 2012), it has the advantage of using a white synchrotron X-ray beam. Recently, we demonstrated that the application of a fringe scan can improve the spatial resolution and signal-tonoise ratio of the tomograms obtained in grating-based X-ray interferometry, and successfully realized quantitative X-ray phase tomography for a rotating sample with millisecondorder measurement time (Yashiro et al, 2018a). A higher temporal resolution can be realized with a higher sample rotation speed, if an X-ray source with higher-brilliance, such as an undulator or an X-ray free-electron laser, is used (Rack et al, 2014;Olbinado et al, 2017Olbinado et al, , 2018Escauriza et al, 2018;Vagovič et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the measurement period of DEI could not be shortened, and time-resolved observations such as in vivo and/or operando observations could not be performed. GXI has a similar limitation, and it was broken using a combination of continuous fast sample rotations and slow grating movements (Kibayashi et al, 2012;Yashiro et al, 2018). In this article, we report on the principles of fast DEI, a DEI system used in feasibility observations and images obtained of biological samples.…”
Section: Introductionmentioning
confidence: 99%